Impact of mesophilic anaerobic digestion and post-treatment of digestates on the transfer of conjugative antimicrobial resistance plasmids. (October 2022) - Kempf, Isabelle; Le Devendec, Laetitia; Lucas, Pierrick; Druilhe, Céline; Pourcher, Anne-Marie
Highlights: We analysed raw manure samples, mesophilic anaerobic digestates and post-digestates. Plasmids were transferred from raw manure but not from digestates or post-digestates. Conjugative Enterobacterales plasmids conferred resistance to various antibiotics. Mesophilic AD processes lead to fewer conjugative Enterobacterales plasmids. Care must be taken to avoid re-contamination during storage. Abstract: Manure is a major source of antimicrobial-resistant bacteria and resistance genes carried by mobile genetic elements such as plasmids. In France, the number of on-farm biogas plants has increased significantly in recent years. Our study investigated the impact of mesophilic anaerobic digestion (AD) and the post-treatment of digestates on the fate of conjugative plasmids, along with their potential transfer of antimicrobial resistance. Samples of raw manure, digestates and post-treated digestates were collected from three on-farm biogas plants. Conjugative plasmids were captured using the Escherichia coli CV601 recipient strain and media supplemented with rifampicin and kanamycin — to which the recipient strain is resistant — and tetracycline, sulfamethoxazole, gentamicin, trimethoprim, amoxicillin, cefotaxime, ciprofloxacin or colistin. Putative transconjugants were identified and characterised by disc diffusion and whole genome sequencing. The results showed that the antimicrobial resistance genes transferred from the different matrices conferred resistance to tetracyclines, sulphonamides, trimethoprim, and/or streptomycin. Transconjugants were obtained from raw manure samples but not from digestates or post-digestates, suggesting that mesophilic AD processes may produce fewer conjugative plasmids potentially able to be transferred to Enterobacterales.